Computed tomography angiography in chronic coronary syndrome: Association to catheterization laboratory activity and survival - Leif Thuesen; Bjarne Linde Nørgaard; Marc Meller Søndergaard; Kristian Hay Kragholm; Martin Kirk Christensen; Mariann Tang; Carl-Johan Jakobsen (American Heart Journal Plus, 2025)
Study objective: To investigate catheterization laboratory efficiency and mortality in chronic coronary syndrome (CCS) patients before and after introduction of coronary computed tomography angiography (CCTA). Design: Registry study. Setting: Western Denmark Heart Registry. Participants: We included all first entry adults with suspected CCS undergoing invasive coronary angiography (ICA) or CCTA from year 2000 through year 2020 in Western Denmark. There was a total of 142.815 procedures (ICA 68.640, CCTA, 74.175, and revascularization 32.311 procedures). Interventions: ICA, CCTA and coronary revascularization by percutaneous coronary intervention or coronary arterial bypass grafting. Main outcome measures: The use of ICA and CCTA, revascularization by PCI or CABG, catheterization laboratory efficiency (revascularization/ICA ratio), and all-cause mortality. Results: During the study period, the percentage of revascularized patients decreased from 45.7 % to 13.3 %, because of increasing use of CCTA. The revascularization/ICA ratio decreased from 46.3 % to 40.1 %. In all CCTA-first patients, 2.7 % of women and 6.9 % of men had a revascularization procedure within 6 months. One- and five-year mortality in revascularized patients decreased by 56 % and 4 % and in non-revascularized patients diagnosed with ICA first by 49 % and 26 %, respectively. Both revascularized and non-revascularized patients had better survival than the background population. Conclusions: The extensive use of CCTA did not reduce the number of ICA procedures without subsequent revascularization, and few CCTA-first patient had a subsequent revascularization procedure. We found increased survival in CCTA/ICA diagnosticated patients as compared to the background population possibly due to better prognostication and general treatment in these patients.